Comparison of Two SARS-CoV-2 Rapid Antigen Test - Stefany Boroh; Irda Handayani; Nursin Abdul Kadir; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
The Coronavirus Disease 2019 (COVID-19) pandemic continues to spread worldwide. A quick, simple, and accurate test to diagnose COVID-19 is essential for this situation. This study aims to evaluate and compare the rapid antigen examination of SARS-CoV-2 with Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) in detecting SARS-CoV-2. A retrospective study with a cross-sectional approach using medical record data from suspected, controlled, and confirmed COVID-19 patients whose samples were taken simultaneously for rapid antigen examination of SARS-CoV-2 (SD-Biosensor and Lungene) and RT-PCR at Labuang Baji Hospital, Makassar from September 2020-September 2021. Each instrument's sensitivity, specificity, negative predictive value, and positive predictive value were analyzed with the Receiver Operating Characteristics (ROC) curve method. This study obtained data from 312 rapid antigen tests for SARS-CoV-2, divided into two categories, 98 using Lungene and 214 using SD-Biosensor. Rapid antigen Lungene had a sensitivity of 71.4%, specificity of 71.4%, an accuracy of 71.4%, and a 31 reactive result in CT value. The SD-Biosensor Rapid antigen had a sensitivity of 62.6%, a specificity of 99.1%, an accuracy of 82.2%, and a 26 reactive result in CT value. In summary, the sensitivity of rapid antigen Lungene is higher than SD-Biosensor. Specificity and accuracy of rapid antigen SD-Biosensor higher than Lungene. Rapid test antigen SARS-CoV-2 has the potential to be a screening test for COVID-19 as long as the sampling time is right.